Relationship between the presence of certain bacterial pathogens and periodontal status of urban Thai adults - Kitti Torrungruang (2018)
Background: The association between Aggregatibacter actinomycetemcomitans (previously Actinobacillus actinomycetemcomitans), Porphyromonas gingivalis, and Tannerella forsythia (previously T. forsythensis) and periodontal disease has been reported in Western populations. However, corresponding data in Asian populations are still lacking. The aim of this study was to determine the prevalence of these three bacteria and their relationship to periodontal status in a group of urban Thai adults. Methods: The study was conducted in 453 subjects, aged 39 to 59 years. The presence of bacteria in subgingival plaque was analyzed using polymerase chain reaction analysis. Subjects were classified as having chronic periodontitis if they had at least three sites with probing depths ≥5 mm. Logistic regression analysis was used to determine the degree of association between the target bacteria and periodontal status. Results: A. actinomycetemcomitans, P. gingivalis, and T. forsythia were found in 19.0%, 70.9%, and 77.5% of the subjects, respectively. About one-third (36.2%) of subjects had chronic periodontitis. In univariate analysis, age, male gender, current smoking, diabetes, and the presence of A. actinomycetemcomitans or P. gingivalis were positively associated with chronic periodontitis, whereas education and income exhibited inverse associations with chronic periodontitis. In multivariate analysis, education, current smoking, diabetes, and the presence of A. actinomycetemcomitans and P. gingivalis remained significant. The adjusted odds ratios for having chronic periodontitis were 2.5 and 3.4 in subjects positive for A. actinomycetemcomitans and P. gingivalis, respectively. However, no significant association was observed between the presence of T. forsythia and periodontal status. Conclusion: The presence of A. actinomycetemcomitans and P. gingivalis, but not T. forsythia, in subgingival plaque was associated with chronic periodontitis in this group of Thai adults.